Introducing the basic dance style of Mak Yong performance / Azrina Asari - Asari, Azrina (2000)
This thesis discusses the multimedia application focusing on the basic dance stylized in Mak Yong performance design in Malay version. Basically this multimedia application is to give an idea and chance to the user to get closed to our traditional theater Mak Yong especially the basic dance stylized. The objective of the application is to provide better understanding on the basic dance stylized in Mak Yong. The iterative and overlapping prototyping method is adopted in developing the application. This multimedia application is concentrating on the basic dance stylized, but there is also the brief historical of Mak Yong performance and its elements provided. The effective and comprehensive text, colorful photography, exciting digitized video and graphics, and the sound effect are combining together to enables communication be stimulating and exciting. Altogether this multimedia application enables user to learn more easily and exploring the local cultural heritage especially on the Mak Yong basic dance stylized different approach towards the information ages.